Kinetic study of Friedel-Crafts acylation reactions over hierarchical MCM-22 zeolites - Aleixo, Rodrigo (2017)
Friedel-Crafts acylation was studied under mild conditions using hierarchical MCM-22 zeolites prepared by desilication and by desilication + acid treatment, using furan, pyrrole and anisole as substrates, and acetic anhydride as acylating agent. Enhanced catalysis was observed for furan and anisole, especially at short reaction times. Kinetic results modelling using non-linear regressions applied to a simplified Langmuir-Hinshelwood equation showed that desilication treatment followed by acid treatment improved kinetics (higher k and TOF). A QSPR methodology using nine substrate and zeolite descriptors was applied to model kinetics and adsorption. For both processes, the best QSPR model equations lead to the same descriptors, namely, Bronsted acidity, as zeolite's feature, and both van der Waals volume and Dimroth-Reichardt E-T(N) parameter (related to dipolarity and Lewis acidity) as substrates' characteristics. Normalization of descriptors allowed quantification of each descriptor's relative importance leading to a better understanding of the catalytic and adsorption processes.